MOTIVASI BERPRESTASI (STUDI DESKRIPTIF SISWA KELAS V SEKOLAH DASAR NEGERI 4 WRINGIN ANOM SITUBONDO) - Aenor Rofek (Jurnal IKA PGSD (Ikatan Alumni PGSD) UNARS, 2016)
Development in the field of education as a part of national development, need to be realized to the improvement and advancement of the education sector. The decline of the quality of education a lot of scrutiny from the public, participants graduate education, educators and government. Learning is a complex process that happens to everyone and lasts a lifetime. One sign that a person has learned a behavior is a change in him. Changes in the behavior changes which are concerning both knowledge (cognitive) and skills (psychomotor) as well as those concerning values ​​and attitudes (apektif). Such changes should take place as a result of interaction with the environment through the learning process. Where teachers are not the only source of learning, although the tasks, roles and functions in the learning process is very important. Student learning success can be determined by the motivation to learn has. Students who have a high learning motivation will tend achievement high anyway; otherwise students that their motivation for achievement motivation, in this study was defined as the urge to do a task as well as possible by the standards of excellence. SDN 4 Wringin Anom is fairly seeded schools in the district Kec.Panarukan. Situbondo is particularly a willingness to learn it was seen from study participation or attending school student who was always full, the other thing is the kids grade 1-6 students diligently following extra-curricular activities in schools so that the potential motivation can be learned as knowledge about motivation which can be pushed to learn in school. Based on data analysis and discussion can be concluded, that the average achievement motivation and fifth grade students of State Elementary School 4 Wringin Anom Situbondo at high category with a score of 142.